COVID-19 DI TWITTER : SOSIALISASI DAN EDUKASI DAN PERUBAHAN LANSKAP MEDIA - Nina Widyawati; Widjajanti M Santoso; Ikbal Maulana; Ibnu Nadzir Daraini; Ana Windarsih; Purnama Alamsyah (LIPI Press, 2021)
The social media is assumed as canal to get information during the pandemic of COVID-19, however it also indicate the landscape of the media. During the pandemic, social media produces information, however several are inaccurate, therefore it coins new terms such as infodemic. On the other hand, government afraid that it might cause confusion and questioning the legitimate information for the economic and health reasons. The other important assumption is due to its popularity, the social media function as means of education and socialization. Therefore the goals of the study are, first is showing information as education and socialization or as infodemic; second is show actors dominate the social media discussion; third is to map the changing of the media’s landscape. Object of study is twitter during the three stages of PSBB (Pembatasan Sosial Berskala Besar) or large scale social restriction; the first, the transition and the full scale. The result shows that civil society as well as government educate and socialize to prevent the spread of pandemic. However, there are several unpopular infodemic and seldom re-Tweet. Individual plays important role rather that the media indusry, and it indicate the transition period of the media, where the media industry plays important role in the social media’s information due to its dominant Tweet.